SEMI MODUL POLINOMIAL FUZZY ATAS ALJABAR MAX-PLUS FUZZY - Ari Wardayani; Suroto Suroto (Universitas Jenderal Soedirman, 2011)
In this paper, we discuss the extension of fuzzy max-plus algebra on polynomial with coefficient in fuzzy number. We also proof that fuzzy polynomial is semi modul over fuzzy max-plus algebra.